High‐dose busulfan–thiotepa with autologous stem cell transplantation followed by posterior fossa irradiation in young children with classical or incompletely resected medulloblastoma. Issue 5 (28th January 2014) - Bergthold, Guillaume; Kababri, Maria El; Varlet, Pascale; Dhermain, Frederic; Sainte‐Rose, Christian; Raquin, Marie‐Anne; Kieffer, Virginie; Goma, Gisele; Grill, Jacques; Valteau‐Couanet, Dominique; Dufour, Christelle
<x xml:space="preserve">Abstract</x> Background The aim of the study is to evaluate the outcome of young children with high risk localized medulloblastomas (newly diagnosed classical or incompletely resected) treated by high‐dose busulfan–thiotepa with autologous stem cell rescue (ASCT) followed by focal radiation therapy (RT). Procedure Between September 1994 and January 2010, 19 children younger than 5 years old at diagnosis fulfilling the above inclusion criteria were treated at the Institute Gustave Roussy. After conventional chemotherapy, they received busulfan at a dose of 600 mg/m2 and thiotepa at a dose of 900 mg/m2 followed by ASCT. Focal RT was delivered at least 70 days after ASCT. Results The median follow‐up was 40.5 months (range, 14.5–191.2 months). The 3‐year event‐free survival (EFS) and OS were 68% (95% CI 45–84%) and 84% (95% CI 61–94%), respectively. Acute toxicity consisted mainly in hepatic veno‐occlusive disease (6/19 patients) and bone marrow aplasia (all patients). No toxic death occurred. The Full Scale Intellectual Quotient tended to decrease over time at a mean rate of 0.9 point per year from the date of diagnosis. Conclusions This intensive treatment resulted in a high overall survival rate in young children with newly diagnosed non‐metastatic classic or incompletely resected MB. In spite of a high incidence of hepatic veno‐occlusive disease (32%), the acute toxicity was manageable. Delayed neuropsychological side effects remain main concerns. These results should to be confirmed in a larger cohort. Pediatr Blood Cancer 2014;61:907–912. © 2014 Wiley Periodicals, Inc.